Problems in the Arrangement of Household Abandonment Crimes in the PKDRT Law And Its Relevance in Court Decisions - Laili Nur Anisah; Anin Dita (UNISKA LAW REVIEW, 2022)
Domestic neglect is a form of domestic violence that is often encountered in the community, but statistics show this violence is the least violent compared to other forms of violence stipulated in Law number 23 of 2004 on the Elimination of Domestic Violence. The number of household neglects both recorded in the data of women's comnas and in the police is very small, the real number is never known. It can go unreported because it is not considered a form of domestic violence. This research will explore the problem of regulating the regulation of economic neglect violence in Law No. 23 of 2004 on the Elimination of Domestic Violence and what impact the arrangement has on the execution of court decisions. The method used in this study is normative research, using literature studies with primary legal materials of Law 23/2004 and comparing 3 district court rulings that break free cases of domestic neglect violence. The results of this study are known that the regulation of household neglect articles still causes differences in interpretation in its implementation, such as the absence of a deadline for household neglect and the definition of the phrase abandonment in the law.